Processing AlSi10Mg by selective laser melting: parameter optimisation and material characterisation. (May 2015) - Kempen, K.; Thijs, L.; Van Humbeeck, J.; Kruth, J.-P.
<x content-type="archive" xml:space="preserve">Abstract</x> Owing to their attractive combination of mechanical properties, high heat conductivity and low weight, the Al–Si alloys found a large number of applications in the Additive Manufacturing field for automotive, aerospace and domestic industries. However, due to their high reflectivity and heat conductivity, they are harder to process by Selective Laser Melting. This work elaborates on both the optimisation of process parameters, in order to get nearly fully dense parts, and the material properties resulting from this specific material process combination. A process parameter window is defined, in which the formed melt pool is stable and meets the set requirements. In this process window, the parameter set for optimal density is defined. It is shown that AlSi10Mg parts produced by SLM have mechanical properties higher or at least comparable to the cast material because of the very fine microstructure.